THE MARKET CHAIN OF FRUIT PRODUCTION IN SERBIA – A CASE STUDY OF RASPBERRY AND SOUR CHERRY CULTIVATION - Radosavljević, Katica (Economic Annals, 2008)
The trade in fresh and frozen fruit is complex and fragmentary. Currently producers are forced to use a variety of marketing channels - farmers' markets, processing industries, trade companies and brokers. To increase quality, production, profitability and exports, it is essential to maximize cooperation between producers, processors, wholesalers and retailers. Vertically and laterally integrated fruit marketing channels demand the smallest number of intermediaries and direct relations with consumers. In past decades, fruit production in Serbia was characterized by irrational resource allocation. Neglect of the agribusiness marketing concept led to supply shortages. As a result, prices increased while quality decreased. Only integrated marketing concepts can boost quality, yields, profitability and competitiveness.